Efficient dispersion of aggregated extracellular vesicles: a comparative study of water-bath sonication and regular pipetting - Suryeon Kim; Inhwan Oh; Juhyun Kim; Nayeong Lee; Jun Go; Yang Jin; Won June Kim; Heedoo Lee (Scientific Reports)
Abstract Extracellular vesicles (EVs) are nano-sized particles released by various cell types that facilitate intercellular communication by transferring bioactive molecules. Owing to their biocompatibility, EVs are widely used as drug delivery vehicles. However, freezing EVs at – 70 °C can induce aggregation, reducing their effective concentration and drug delivery efficiency. In this study, we evaluated the use of water-bath sonication to disperse aggregated EVs and compared its effectiveness with regular pipetting. Frozen EVs showed reduced total concentration and increased aggregation relative to fresh EVs. Sonication at power level 3 (40 kHz, 100 W) significantly increased EV concentration and reduced aggregation. Unlike pipetting, only sonication effectively dispersed aggregated EVs, though subsequent pipetting caused reaggregation. In vivo, aggregated EVs were detected in the bronchoalveolar lavage fluid of mice treated with frozen EVs, whereas mice receiving sonicated EVs exhibited fewer aggregates and enhanced cellular uptake. Molecular dynamics simulations supported the effectiveness of sonication in dispersing EVs. In conclusion, water-bath sonication is a simple and effective method to restore the functionality of freeze-thawed EVs, improving their intracellular delivery and therapeutic potential.